Nuestro Hospital Universitario - Vivaldi V., Ennio (Revista Hospital Clínico Universidad de Chile, 2009)
To speak about “our university hospital”, integrates automatically the history, the derived social responsibility and an essential academic project which persistence will depend on its own initiative, creativity and coherence in accomplishing specific objects. In the conceptual and action frame exposed by the Faculty ViceDean, he established the proposals, strategies and resolutions pretended to be perdurable in the long follow up, as a concrete expression of the professional and educational mission of its community.